Use and Effectiveness of ICT Tools in Disaster Management: A Case of Kenya Red Cross Society - Mung‘ou , Cherotich (African Journal of Education,Science and Technology (AJEST), 2014)
Information and communications technology (ICT) can potentially play a pivotal role in disaster prevention, mitigation and management. For instance, remote sensing for early warning is made possible by various available technologies, including telecommunication satellites, radar, telemetry and meteorology. Enhanced early warning systems especially at national and community levels can save many lives and property if managed and implemented well. The Kenya Red Cross Society (KRCS) has been at the forefront in disaster management in Kenya. In the recent past, the society has diversified and invested in the use of modern information communication technologies in addressing myriad disasters. The KRCS investment in ICT for disaster management has been achieved through networking at the headquarters, regional and branch offices countrywide. This paper therefore sought to explore the use of ICT tools in disaster management and its effectiveness in Kenya Red Cross Society. Questionnaires, key informant interviews, structured interviews and secondary data analysis (content analysis) were the sources of information used. The overall research design was mainly qualitative in nature; adopting a case study approach. Purposive sampling was used to select Kenya Red Cross society for this study due to its participation in ICT based disaster management. The findings indicated that ICT facilities used by the Kenya Red Cross Society in disaster management are mainly HF radios and butterfly cameras, located in Nairobi. HF radios are the most effective tools used in disaster management; however there is inadequate investment in ICT tools for disaster management by the Kenya Red Cross Society. The author recommends more government support and more investment towards the use of ICT in disaster management.